The perception of Malaysian pedestrians toward the use of footbridges - Hasan, R. (Taylor and Francis Inc., 2018)
Objective: The footbridge is a vital structure in the road network and a cornerstone among crossing facilities. Yet, it suffers from low usage by pedestrians as they try to cross the street on the level. This study aims to analyze the perceptions of Malaysian pedestrians toward the use of footbridges with the consideration of different factors. Method: The study was carried out by collecting data from field observation and questionnaire distribution on the street among the public. The data were statistically analyzed by applying multiple linear regression models and a series of chi-square tests. Results: The study found that the most influential factor cited by pedestrians in decision making regarding using a footbridge is the existence of an escalator. Being in a hurry and the fear of heights were significantly associated with choosing not to use a footbridge. Zebra crossing was chosen as the most favorable type of crossing facility by the majority of respondents. In addition, installation of a fence and barriers was proposed as an effective procedure to prevent jaywalking. To construct new and efficient footbridges in the future, the study suggests consideration of traffic volume, posted speed limit, and the number of lanes, because these are the most influential factors to predict the usage rate. Conclusions: The study encourages decision makers and stakeholders to consider providing escalators for new footbridges to enhance the safety of pedestrians. Â© 2018 Taylor & Francis Group, LLC.